2023
DOI: 10.3389/fimmu.2023.1075970
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hsa_circRNA_100632 as a novel molecular biomarker for fulminant type 1 diabetes

Abstract: ObjectiveCircular RNAs (circRNAs) are associated with diabetes, but their role in fulminant type 1 diabetes (FT1D) is unclear. Thus, we characterized the role of circRNAs in FT1D.Research design and methodsCircRNA expression profiles were detected in peripheral blood mononuclear cells (PBMCs) of five FT1D patients and five controls using a circRNA microarray. An independent cohort comprised of 40 FT1D cases, 75 type 1 diabetes (T1D) cases, and 115 controls was used to verify the circRNAs using quantitative rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…39 Yin et al reported that the expression level of hsa_circRNA_100,632 was upregulated in the PBMCs of FT1D patients and may be related to the altered cellular immunity in patients with FT1D. 40…”
Section: Cellular Immunitymentioning
confidence: 99%
“…39 Yin et al reported that the expression level of hsa_circRNA_100,632 was upregulated in the PBMCs of FT1D patients and may be related to the altered cellular immunity in patients with FT1D. 40…”
Section: Cellular Immunitymentioning
confidence: 99%